2007
DOI: 10.1177/0731684407083951
|View full text |Cite
|
Sign up to set email alerts
|

Polycarbonate/Short Glass Fiber Reinforced Composites — Physico-mechanical, Morphological and FEM Analysis

Abstract: A series of polycarbonate (PC), reinforced with short glass fiber (SGF) in different weight ratios viz., 10, 20 and 30%, has been fabricated by melt mixing with the aid of a twin screw extruder, in order to study the influence of glass fiber reinforcement on PC. The test specimens were fabricated as per ASTM standards and evaluated for their physico-mechanical properties. Incorporation of short glass fiber to PC enhances the tensile behavior of the composites significantly. The morphological behavior of PC com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 5 publications
0
8
0
Order By: Relevance
“…From the overall observations, the impregnation of fiber content in the polymer influences the properties of the composites. 32 In this study, flexural strength of the hybrid composite increases with increase in fiber content reaches the maximum value for 12 wt% basalt fiber. In injection molded composites it is difficult to determine the fiber orientation factor because it is function of the geometry, processing conditions and material composition.…”
Section: Results Of Testingmentioning
confidence: 50%
“…From the overall observations, the impregnation of fiber content in the polymer influences the properties of the composites. 32 In this study, flexural strength of the hybrid composite increases with increase in fiber content reaches the maximum value for 12 wt% basalt fiber. In injection molded composites it is difficult to determine the fiber orientation factor because it is function of the geometry, processing conditions and material composition.…”
Section: Results Of Testingmentioning
confidence: 50%
“…As shown in Figure 6(a), compared with untreated samples, the impact strength increased greatly to nearly 80 kJ/m 2 by 700% when press temperature was between 20°C and 90°C, compressed at 5 mm/s. Interestingly, this pure PC was excellent due to its maximum strength reaching or even surpassing the properties of some PC composites 3,13 . However, the value of strength began to decrease to 60 kJ/m 2 as temperature ascended to 120°C.…”
Section: Resultsmentioning
confidence: 94%
“…Considerable studies demonstrated the approach of adding fillers, which combine PC with other fibers or particles to obtain high strength 1,13,14 . Jawali et al 13 prepared a series of PCs reinforced by short glass fibers through melt processing of a twin screw extruder. The results indicated that the tensile strength, elastic modulus and bearing capacity of composites improved significantly.…”
Section: Introductionmentioning
confidence: 99%
“…The optimum weight percentage of BF and CQ was found to be 12% and 0.5% respectively that augmented the mechanical properties of the composites. 38 Thus, PBCQ 2 shows high mechanical effective mechanical properties compared to less filled silane-treated basalt fibers and CQ fibers PBCQ 1 and PBCQ 3 composites. 41
Figure 9.SEM image of (a) fractured PBCQ 1 impact specimens; (b) fractured PBCQ 2 impact specimens; (c) fractured PBCQ 3 impact specimens.
…”
Section: Discussion On Experimental Resultsmentioning
confidence: 95%
“…37 In this study, it is clearly identified that the increase in the BF content (12 wt%) in PLA in the polymer composite with 0.5 wt% of CQ exhibits better flexural strength. 38…”
Section: Discussion On Experimental Resultsmentioning
confidence: 99%